PEMBUATAN PAKAN TERNAK FERMENTASI DAN PENERAPAN ZERO WASTE SEBAGAI UPAYA PEMBERDAYAAN PETERNAK AYAM BROILER DI KABUPATEN BONDOWOSO - Nidya Shara Mahardika; Dyah Ayu Savitri; Andrew Setiawan Rusdianto (UPT Penerbitan Universitas Jember, 2018)
The availability and price of animal feed have become big obstacles in developing animal husbandry, especially for broiler chickens. Broiler chicken requires more than 40 chemical ingredients for its feed supplementation by protein content of 19.5-21%. A strategy could be conducted by combining tofu solid waste and rice bran as the main ingredients in animal feed production. Tofu solid waste and rice bran showing the protein content of 17.4% and 12%, lipid content of 5.9% and 12.1%, and crude fiber content of 16.8% and 13%, respectively. The utilization of those components fulfilling the necessity of animal feed. They also have a relatively cheap price and easy to obtain, so they are highly potential to be used as substitution for animal feed. Partners in this program were two chicken farmers (Firqin Fatahillah and Miqdad Mauladi) located in Tlogosari village, Tlogosari sub-district, Bondowoso regency. The problems coped by the farmers were : (a) a high price of animal feed which resulting in the low value of benefit, (b) the minimal processing method of excrement of chickens, (c) the high risk of production of chicken broiler threathened by some diseases and price fluctuation. The solution for those problems were (1) the application of science and technology in the production of fermented animal feed made from tofu solid waste and rice bran, (2) the application of zero waste principles, (3) the application of risk management.